Clinical Impact of Switching from Conventional to Bactec Blood Culture System in a Hospital Setting - Gupta, Ravi Shankar; Shidiki, Amrullah (NPRC Journal of Multidisciplinary Research, 2025)
Background: Bloodstream infections (BSIs) leading to sepsis remain major causes of morbidity and mortality in hospitalized patients worldwide. Conventional blood culture methods, though regarded as the diagnostic gold standard, require prolonged incubation and manual monitoring, which delay the detection of microbial growth and the initiation of targeted therapy. The BACTEC Automated Blood Culture System (Becton Dickinson, USA) has been developed to address these limitations through continuous monitoring of carbon dioxide (CO₂) production using a fluorescent sensor, allowing rapid and reliable detection of microbial growth. This study aimed to evaluate the clinical impact of switching from the Conventional Blood Culture Method to the BACTEC System in a tertiary care hospital setting in Nepal. Methods: A total of 150 blood samples were analyzed—75 using the Conventional Method and 75 using the BACTEC System—to compare time to detection, positivity rate, contamination rate, turnaround time, and early clinical response. Results: The BACTEC system significantly reduced mean time to detection from 48.3 ± 8.7 hours to 18.6 ± 4.2 hours (p < 0.001), increased culture positivity from 34.7% to 50.7% (p = 0.03), and decreased contamination from 8.0% to 2.7% (p = 0.04). Antibiotic therapy was changed based on BACTEC results in 46.6% of patients, compared to 25.3% in the conventional group (p = 0.01). Conclusion: The findings indicate that the BACTEC Blood Culture System enhances diagnostic efficiency, accelerates clinical decision-making, reduces unnecessary empirical therapy, and supports antimicrobial stewardship. It represents a reliable, cost-effective solution for improving patient outcomes in resource-limited hospital settings. Novelty: Introducing automated blood culture testing strengthens diagnostic turnaround and supports earlier targeted therapy in a tertiary hospital with limited resources.